2021
DOI: 10.3390/pr9111923
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Roasting Parameters for Recovery of Vanadium and Tungsten from Spent SCR Catalyst with Composite Roasting

Abstract: Every year, large amounts of selective catalytic reduction (SCR) catalysts with losing catalytic activity and failing to be regenerated need to be regenerated, which will result in acute pollution. Recycling valuable metals from spent SCR catalysts can not only solve environmental problems, but also save resources. The process of sodium roasting and water leaching is able to effectively extract vanadium (V) and tungsten (W) from spent SCR catalysts. To improve the efficiencies of V and W, different sodium addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These results show that roasting time has a direct impact on the leaching efficiency of uranium, copper and cadmium with leaching efficiency increasing from 80%, 75%, and 70 to 90%, 89%, and 83% at 3 h, respectively. At 4 h, the metal values' leaching efficiency decreases because roasted ore showed caking, which caused leaching of part elements to become more difficult [55]. Thus, 3 h considered as the best roasting time.…”
Section: Effect Of Roasting Temperaturementioning
confidence: 99%
“…These results show that roasting time has a direct impact on the leaching efficiency of uranium, copper and cadmium with leaching efficiency increasing from 80%, 75%, and 70 to 90%, 89%, and 83% at 3 h, respectively. At 4 h, the metal values' leaching efficiency decreases because roasted ore showed caking, which caused leaching of part elements to become more difficult [55]. Thus, 3 h considered as the best roasting time.…”
Section: Effect Of Roasting Temperaturementioning
confidence: 99%
“…The leaching residues of nano-TiO 2 and sodium titanate nanowires were also used as heavy metal adsorbents. The addition of NaCl allowed decomposition-generated chlorine Cl 2 to act as a catalyst and oxidant to promote the oxidation of low-valent V, thus facilitating the leaching of V. Wang et al 103 compared different types of sodium additives and found that the leaching efficiency of NaOH−NaCl roasting for V and W was up to 91.39% and 98.26% higher compared to acid and alkaline leaching, respectively. At the same time, the addition of low melting point NaOH promoted the reaction to a greater extent than the addition of sodium additives with different melting points.…”
Section: 22b Compound Salt Meltingmentioning
confidence: 99%
“…8 This system shows excellent catalytic properties, such as a wide operating temperature window and high denitration rate. 9 Spent SCR catalysts are increasingly generated from corresponding industrial sectors 10,11 and are gaining more attention given their very high concentration of strategic as well as base metals like vanadium, tungsten, and titanium. 12 The spent SCR catalyst is subjected to recycling through an integrated hydrometallurgical route 13,14 to recover the valuable metal and simultaneously address the resulting global environmental issues.…”
Section: Introductionmentioning
confidence: 99%